ELECTRICAL VESTIBULAR NERVE STIMULATION FOR THE MANAGEMENT OF TENSION HEADACHE: Electrical Vestibular Nerve Stimulation for the Management of Tension Head-ache - SAI SAILESH KUMAR GOOTHY; SRILATHA GOOTHY; JASON MCKEOWN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Tension headache is the most common type of headache and typically it is described as pain or pressure in the head, scalp, or neck, often associated with localized muscle discomfort. It was hypothesized that stimulation of vestibular nerve may relieve pain. In this single-person study, vestibular nerve stimulation was administered daily for a period of 6 weeks. The participant was an 18 years male with a 4 years history of moderate headache at least once week and with repeated periods of moderate stress. He was under medications; however, the pain was not relieved. Stress levels were measured using DASS 21 scale. Pain was measured using pain scale, autonomic, and cognitive parameters recorded by standard methods. During this study, the participant reported a significant reduction in both the frequency and intensity of headaches and by the end of the 6 weeks of the study, it was noticed that he reduced the usage of pain medication. Autonomic parameters remained within normal limits after the periods of stimulation and cognitive functions were improved. This study suggests that electrical stimulation of the vestibular nerve may help to reduce tension headache and highlights the need for larger studies in this area and further exploratory studies in the management of other regional pain such as orofacial pain, dental pain, and management of pain after mandibular surgery.